Validation of the Stolwijk and Tanabe Human Thermoregulation Models for Predicting Local Skin Temperatures of Older People under Thermal Transient Conditions - Yin Tang; Hang Yu; Zi Wang; Maohui Luo; Chaoen Li (Energies, 2020)
Human thermoregulation models can predict human thermal responses to evaluate thermal comfort and help create a healthy environment, while their applicability to older people has not been sufficiently validated. This study aimed to evaluate the performance of the Stolwijk model and the Tanabe model for predicting older people’s mean and local skin temperatures under thermal transient conditions. Eighteen healthy older people were recruited and exposed to transient environments including neutral (26 °C), low-temperature (23 and 21 °C), and high-temperature (29 and 32 °C) conditions. The local skin temperatures of the subjects were measured and compared to predictions of the Stolwijk model and the Tanabe model. The results revealed that the Stolwijk model and the Tanabe model could accurately predict the mean skin temperature of older people under neutral and high-temperature conditions, while their predictive accuracy declined under low-temperature conditions. Increased deviations were observed in the predictions of local skin temperatures for all conditions. This work attempted to provide an understanding of older people’s thermal response characteristics under transient conditions and to inspire the improvement of thermoregulation models for older people.